Identification and Characterization of New Bacteriophages to Control Multidrug-Resistant Pseudomonas aeruginosa Biofilm on Endotracheal Tubes - Oliveira, Viviane C.; Bim, Felipe L.; Monteiro, Rachel M.; Macedo, Ana Paula; Santos, Emerson S.; Silva-Lovato, Cláudia H.; Paranhos, Helena F. O.; Melo, Luís D. R.; Santos, Sílvio B.; Watanabe, Evandro (Frontiers in Microbiology, 2020)
Studies involving antimicrobial-coated endotracheal tubes are scarce, and new approaches to control multidrug-resistant Pseudomonas aeruginosa biofilm on these devices should be investigated. In this study, five new P. aeruginosa bacteriophages from domestic sewage were isolated. All of them belong to the order Caudovirales, Myoviridae family. They are pH and heat stable and produce from 27 to 46 particles after a latent period of 30 min at 37oC. Their dsDNA genome (ranging from ⁓62 kb to ⁓65 kb), encode from 65 to 89 different putative proteins. They exhibit a broad lytic spectrum and infect 69.7% of the P. aeruginosa strains tested. All bacteriophages were able to reduce the growth of P. aeruginosa strains in the planktonic form. Bacteriophages were also able to reduce biofilm viability rates and metabolic activity of P. aeruginosa strains in a model of biofilms associated with endotracheal tubes. In addition, scanning electron microscopy micrographs showed disrupted biofilms and cell debris after treatment of bacteriophages revealing a remarkable biofilm reduction. The lytic activity on multidrug-resistant P. aeruginosa biofilm indicates that the isolated bacteriophages might be considered good candidates for therapeutic studies and for the application of bacteriophage-encoded products.